Сучасні напрями функціонування сфери туризму в Україні - Збарський, В. К.; Грибова, Діана Вікторівна; Грибова, Диана Викторовна; Hrybova, Diana (My University, 2020)
UK: У статті досліджено сучасний стан та напрями розвитку туристичної галузі в Україні. Зазначено роль екологічних чинників у процесі забезпечення ефективного функціонування туристичного бізнесу. Обгрунтовано необхідність запровадження заходів щодо формування серед населення поведінкової моделі рекреаційного природокористування. Вона має бути спрямована на усвідомлення важливості дбайливого ставлення до навколишнього середовища в бізнесовій діяльності, а також в особистому житті. Вказується на факт існування великої проблеми в процесі формування іміджу України за кордоном. Зазначається, що державна стратегія та грошова підтримка практично не спрямовані на підвищення ефективності маркетингу країни для іноземців. Вказується, що уряду слід подбати про зниження непрямих податків у авіаційному та готельному бізнесі, що значно вплине на кількість туристичного прибуття в країну. Наголошується на особливому значенні інфраструктурного забезпечення надання туристичних послуг. Виділено такі напрями покращення конкурентоспроможності туризму в Україні: визнання туристичної галузі одним з пріоритетів держави; оптимізація системи нормативного забезпечення природокористування; розвиток інфраструктурного забезпечення. EN: The article investigates the current state and directions of tourism industry development in Ukraine. The role of environmental factors in the process of ensuring the efficient functioning of the tourism business is outlined. The necessity of introducing measures to form a behavioral model of recreational nature use among the population is substantiated. It should be aimed at recognizing the importance of caring for the environment in business as well as in personal life. The fact that there is a big problem in the process of forming the image of Ukraine abroad is pointed out. It is noted that the state strategy and financial support are practically not aimed at improving the country's marketing effectiveness for foreigners. It is stated that the government should take care to reduce indirect taxes in the aviation and hotel business, which will significantly affect the number of tourist arrivals in the country. The importance of infrastructure for the provision of tourist services is emphasized. It is noted that with the right offer to tourists of all alternatives of accommodation, the level of differentiation of tourists increases, which in the future will positively affect the socio-economic development of the tourism industry. In order to establish the closeness of Ukraine's tourism potential with other countries and the similarity of competitive indicators, direct tourism factors were analyzed. It has been proven that Spain, France and Germany are the center of tourism in the peripheral structure of tourism, while Ukraine is the tourist periphery of Europe. The very low rate of arrival, due to the lack of continuous generation of organizational and marketing innovations in the tourism industry, causes a low share of cash inflows from the industry, compared with the leading countries. It is noted that potentially Ukraine has no worse factor potential than the leading countries. However, in reality, the neglect of this sector of the economy demonstrates a significant lag in the tourism potential of Ukraine from the potential of European landmarks. The following directions of improvement of competitiveness of tourism in Ukraine are highlighted: recognition of the tourism industry as one of the priorities of the state; optimization of the system of regulatory support of environmental management; development of infrastructure support.
Current directions of functioning of tourism in Ukraine
Keywords: туристичний бізнес; інтегральний показник конкурентоспроможність; світовий рейтинг; рекреаційне природокористування; інвестиційна привабливість; tourism business; integral competitiveness indicator; world rating; recreational nature management; investment attractiveness